Deteksi Masker Wajah Menggunakan Metode Adjacent Evaluation Local Binary Patterns - Randy Wihandika (Ikatan Ahli Informatika Indonesia (IAII), 2021)
The COVID-19 pandemic is still ongoing until 2021 and is likely to continue until an uncertain time. This arises because the spread of the SARS-CoV-2 virus also continued to occur in the community. Of the five points in 5M that has been initiated by the government, the focus of this study is the use of face masks. In this study, an image-based automatic mask detection method using a classification approach is proposed. This method can be used in automated systems to increase public discipline in wearing masks to suppress the spread of the SARS-CoV-2 virus. The classes used in the classification are